The Hyperphagia Questionnaire: Insights From a Multicentric Validation Study in Individuals With Prader Willi Syndrome - Licenziati, Maria Rosaria; Bacchini, Dario; Crinò, Antonino; Grugni, Graziano; Fintini, Danilo; Osimani, Sara; Ragusa, Letizia; Sacco, Michele; Iughetti, Lorenzo; De Sanctis, Luisa; Franzese, Adriana; Wasniewska, Malgorzata Gabriela; et al. (Frontiers in Pediatrics, 2022)
Background/objectives: The present study aimed to validate the Italian version of the Hyperphagia Questionnaire (HQ), a 11-items questionnaire developed to assess hyperphagia in individuals with Prader-Willi syndrome (PWS), a complex neurodevelopmental disorder including endocrine dysfunction, hypotonia, intellectual disability, psychiatric disorders and obesity. Methods: Parents of 219 PWS individuals (age range 3-54 years; Mage=17.90; 108 Males), recruited in 12 hospitals in Italy responded to HQ during routine visits. In function of the level of analysis the sample was divided into two groups (<18> years) and into four age-groups (2.5-4.5; 4.5- 8; 8-18; > 18 years) corresponding to different clinical stages. Results: Confirmatory factor analysis (CFA) confirmed the three hyperphagic subdimensions of the original structure (behavior, drive, and severity), but one item was dropped out, reducing the final version to 10 items. Using multi-group CFA, HQ showed satisfactory indexes of measurement invariance by age. Good indexes of internal consistency for each subdimension were found (Cronbach’s alpha and McDonald’s Omega coefficients). The three hyperphagia subdimensions positively converged with other food-related measures: emotional overeating, food enjoyment, food responsiveness, and satiety responsiveness. A significant increase of all hyperphagic subdimensions was found across age groups. Higher hyperphagic levels were found in participants with higher body mass index. Hyperphagic behavior differently increased in function of the interaction between age and underlying genetic mechanisms. Conclusion: The Italian version of the HQ is a psychometrically valid and reliable instrument for assessing hyperphagia in PWS individuals, which may prove useful to evaluate the efficacy of pharmacologic and rehabilitative treatment.